Recovery of Theta Frequency Oscillations in Rats Following Lateral Fluid Percussion Corresponds With a Mild Cognitive Phenotype - Ondek, Katelynn; Pevzner, Aleksandr; Tercovich, Kayleen; Schedlbauer, Amber M.; Izadi, Ali; Ekstrom, Arne D.; Cowen, Stephen L.; Shahlaie, Kiarash; Gurkoff, Gene G. (Frontiers in Neurology, 2020)
Whether from a fall, sports concussion, or even combat injury, there is a critical need to identify when an individual is able to return to play or work following traumatic brain injury (TBI). Currently, there are no objective, non-invasive, rapid, and cost-effective prognostic tools that demonstrate recovery of function. Electroencephalogram (EEG) and local field potentials (LFP) represent potential tools to monitor circuit-level abnormalities related to learning and memory: specifically, theta oscillations can be readily observed and play a critical role in cognition. Following moderate traumatic brain injury in the rat, lasting changes in theta oscillations coincide with deficits in spatial learning. We hypothesized, therefore, that we could use theta oscillations as a biomarker of recovery. In the current study, LFP were recorded from dorsal hippocampus and anterior cingulate in awake, behaving adult Sprague Dawley rats in both a novel environment on post-injury days 3 and 7, and Barnes maze spatial navigation on post-injury days 8-11. Theta oscillations, as measured by power, theta-delta ratio, peak theta frequency, and phase coherence, were significantly altered on day 3, but had largely recovered by day 7 post-injury. Injured rats were not different from shams on the Barnes maze as measured by escape latency, although they did use suboptimal search strategies. Combined with our previous findings, these data suggest that neural oscillations, and particularly theta oscillations, have potential as a biomarker to monitor recovery of brain function following TBI. Specifically, we now demonstrate that oscillations are depressed following injury, but as oscillations recover, so does behavior. Therefore, oscillatory activity represents a potential rapid, cost-effective and objective prognostic biomarker for return to activity decisions.